Digital Transformation in Accounting: Strategies to Enhance the Adoption of Technology-Based Record-Keeping Systems by Micro, Small, and Medium Enterprises (MSMEs) - Ringan, Angelina Yenny; Paluala, Kusman; Sianturi, Meisya Gabeuli (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the main drivers of Indonesia’s economy, but continue to face limitations in financial management due to the dominance of non-standardized manual record-keeping. Digital transformation in accounting emerges as an opportunity to improve efficiency, accuracy, and access to financing through technology-based recording systems. This study aims to analyze the factors influencing MSMEs’ readiness to adopt digital accounting technologies by employing an extended Technology Acceptance Model (TAM), incorporating digital literacy and technological experience as additional variables. A quantitative explanatory research design was applied, involving 96 respondents, including MSME owners and managers in Kendari City across the trade, service, and manufacturing sectors. Multiple linear regression analysis reveals that technological experience and perceived usefulness significantly influence adoption readiness, whereas digital literacy and perceived ease of use show no significant effect. Furthermore, Analysis of Variance (ANOVA) identifies differences in readiness across MSME sectors, particularly between the fashion and culinary industries. These findings underscore the critical role of hands-on technological experience and confidence in practical benefits as key drivers of adoption. This study contributes to the growing body of literature on technology adoption among Indonesian MSMEs. It offers practical implications for policymakers, accounting application providers, and MSME actors in designing strategies to enhance financial digitalization.